Sum

Solve the following sets of simultaneous equations.

*x* +* y* = 4 ; 2*x -* 5*y* = 1

Advertisement Remove all ads

#### Solution

x + y = 4 .....(I)

2x - 5y = 1 .....(II)

From (I) we have

x = 4 - y

Putting this value of x in (II)

2 ( 4 - y ) - 5y = 1

⇒ 8 - 2y - 5y = 1

⇒ 8 - 7y = 1

⇒ 8 - 1 = 7y

⇒ 7 = 7y

⇒ y = 1.

Putting the value of *y *in (I) we have

x + 1 = 4

⇒ x = 3

Thus, ( x , y ) = ( 3,1 )

Is there an error in this question or solution?

Advertisement Remove all ads

#### APPEARS IN

Advertisement Remove all ads

Advertisement Remove all ads